Cluster Headache Secondary to Macroprolactinoma with Ipsilateral Cavernous Sinus Invasion - M. J. Levy; I. Robertson; T. A. Howlett (Case Reports in Neurological Medicine)
We present a 25 year-old man with episodic cluster headache that was refractory to all standard pharmacological prophylactic and abortive treatments. Because of the lack of response, an MRI brain was performed which showed a large pituitary tumour with ipsilateral cavernous sinus invasion. The serum prolactin was significantly elevated at 54,700 miU/L (50–400) confirming a macro-prolactinoma. Within a few days of cabergoline therapy the headache resolved. He continues to be headache free several years after starting the dopamine agonist. This case highlights the importance of imaging the pituitary fossa in patients with refractory cluster headache, It also raises the potential anatomical importance of the cavernous sinus in pituitary-associated headache.